José María de Llanos, un jesuita fundador: 25 años de ausencia - Delgado Rosa, Juan Antonio (Cauriensia, 2017)
Within the Jesuit Jose Maria de Llanos, conflict and peace coexisted at the same time, the affable remembrance of others with the self-surpassing boredom, projectively beginning his frenetic and abundant stage of founding, which he himself will define as the "gallop of the university foundations and Franco". Foundations that will finally lead him to go to the Well of the working depths, the miserable misery, the dung.